2013
DOI: 10.5950/0738-1360-28.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Markov-Perfect Rent Dissipation in Rights-Based Fisheries

Abstract: We present a general, dynamic model of within-season harvesting competition in a fishery managed with individual transferable quotas. Markov-Perfect equilibrium harvesting and quota purchase strategies are derived using numerical collocation methods. We identify rent loss caused by a heterogeneous-in-value fish stock, congestion on the fishing ground, revenue competition and stock uncertainty. Our results show that biological, technological and market conditions under which rents will be dissipated in a standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Discounting and stock effects create incentives to harvest more of the TAC early in the season; endogenous price encourages spreading the harvest more uniformly over the season; biological aggregations create incentives to concentrate harvest due to lower harvest cost; and effort constraints generally spread out the harvest. These results are consistent with existing literature on within-season harvest in catch share fisheries (Boyce, 1992;Valcu and Weninger, 2013). Still, it is worthwhile to emphasize how much harvest patterns can vary depending on market conditions, stock characteristics, and harvesting capacity even in this simple setting.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Discounting and stock effects create incentives to harvest more of the TAC early in the season; endogenous price encourages spreading the harvest more uniformly over the season; biological aggregations create incentives to concentrate harvest due to lower harvest cost; and effort constraints generally spread out the harvest. These results are consistent with existing literature on within-season harvest in catch share fisheries (Boyce, 1992;Valcu and Weninger, 2013). Still, it is worthwhile to emphasize how much harvest patterns can vary depending on market conditions, stock characteristics, and harvesting capacity even in this simple setting.…”
Section: Discussionsupporting
confidence: 90%
“…Timing of catch within the fishing year can have important implications for revenues generated by the fishery, product forms, and response of the fishery to policy changes (Grafton, Squires, and Fox 2000;Homans and Wilen 2005;Smith, Zhang, and Coleman 2008;Huang and Smith 2014). Some theoretical and empirical bioeconomic models have demonstrated the importance of within-season incentives-including biological conditions, stock effects, discounting, seafood markets, and congestion externalities-in determining these catch patterns (Clark, 1980;Boyce, 1992;Fell, 2009;Valcu and Weninger, 2013). Empirical bioeconomic studies have further shown that timing within-season harvest to account for these phenomena could generate substantial rent gains (Larkin and Sylvia, 1999;Huang and Smith, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our results strongly support the notion that the tragedy of the commons unfolds at the individual level and within each season. While this result alone may not be surprising in light of the voluminous theoretical literature on the commons as well as theoretical predictions specific to fisheries (Boyce 1992;Valcu and Weninger 2013), we are unaware of any previous empirical study demonstrating that individual strategic and dynamic behavior is the mechanism that drives inefficient use of the commons. In fisheries, the catch phrase to describe this strategic dynamic interaction is the race to fish, and the conventional wisdom amongst fisheries economists is that an individually transferable quota (ITQ) solves the commons problem.…”
Section: Discussionmentioning
confidence: 76%
“…The seasonal interactions between the environment and fishers is often locally well known at the level of stocks [68] or for ecosystems [9, 10], for both industrial [11, 12] and small-scale fisheries [13, 14]. Models have been developed in order to analyse how natural and socio-economic drivers shape the seasonal dynamics of fishing effort, for single- [1517] and multi-species fisheries [18]. In addition, tools that forecast the seasonal dynamic of marine resources are now being implemented to assist management [19].…”
Section: Introductionmentioning
confidence: 99%